O conselho da cidade e o planejamento urbano de São Luís na dimensão da participação - Nogueira, Jussara Martins (2022)
This dissertation analyses the Consil of the City of São Luís in the períod between 2006 and 2010. For the development of this dissertation two investigative methods were used: the survey of literature, that is. recollection of theoretical authors who have servcd as reference; and the collection of data through subjective interviews. This dissertation is comprised of four chapters, considerations and references. Regarding social participation, it was conciuded that it does not take concrete form in the formulation of public policies of city planning